2008
DOI: 10.1002/hep.22471
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte signaling through CXC chemokine receptor‐2 is detrimental to liver recovery after ischemia/reperfusion in mice†

Abstract: CXC chemokines and their receptor, CXC chemokine receptor-2 (CXCR2), are important components of the hepatic inflammatory response to ischemia/reperfusion (I/R). However, direct effects of CXC chemokines on hepatocytes during this response have not been studied. Wild-type and CXCR2 ؊/؊ mice were subjected to 90 minutes of partial hepatic ischemia followed by up to 96 hours of reperfusion. CXCR2 ؊/؊ mice had significantly less liver injury at all reperfusion times compared with wild-type mice. Early neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
111
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 31 publications
10
111
2
2
Order By: Relevance
“…Although the reason for this discrepancy is unclear, the differences between our study and the study by Kamo et al are the hepatic I/R protocol used and the extent of injury. Compared with our study and prior studies on hepatic I/R injury (13,29), it is likely that the I/R protocol by Kamo et al induced excessive inflammation and injury in the liver. These data suggest that the contribution of the inflammasome might depend on the extent of liver injury and the status of inflammatory responses after I/R.…”
Section: Discussioncontrasting
confidence: 84%
“…Although the reason for this discrepancy is unclear, the differences between our study and the study by Kamo et al are the hepatic I/R protocol used and the extent of injury. Compared with our study and prior studies on hepatic I/R injury (13,29), it is likely that the I/R protocol by Kamo et al induced excessive inflammation and injury in the liver. These data suggest that the contribution of the inflammasome might depend on the extent of liver injury and the status of inflammatory responses after I/R.…”
Section: Discussioncontrasting
confidence: 84%
“…We have previously shown that after hepatic I/R, signals for liver recovery/regeneration do not occur until after 24 h of reperfusion (3,22). Accordingly, although no differences were seen in the degree of liver injury as manifested by serum ALT levels and histology after 8 h of reperfusion in this study, TCR-␦ deficiency may have effects on liver recovery and regeneration.…”
Section: Discussioncontrasting
confidence: 53%
“…The liver is one of the most abundant sources of NKT cells among the immune organs, which account for ϳ50% of total ␣␤ T cells in the liver (11). NKT cells are activated by recognizing glycolipid presentation to TCRs by CD1d, a member of the CD1 family of antigen-presenting molecules (22). Originally, it was thought that NKT cells could not play a role in postischemic tissue injury because of the absence of foreign antigen.…”
mentioning
confidence: 99%
“…We previously showed that specific members of the CXC chemokine family are critical mediators in all aspects of the injury, repair, and regeneration processes (2,4,5,17). Our previous work focused on CXC chemokines that contain a glutamic acid-leucinearginine (ELR) motif in their amino terminus, which confers binding specificity to the receptors CXCR1 and CXCR2 (2,17). However, other CXC chemokines may also be involved in the response to hepatic I/R injury.…”
mentioning
confidence: 97%
“…The ischemic insult induces an inflammatory response resulting in acute liver injury that is followed by a reparative phase and subsequent liver regeneration mediated by a complex interaction of growth factors, cytokines, and transcriptional factors (7,22). We previously showed that specific members of the CXC chemokine family are critical mediators in all aspects of the injury, repair, and regeneration processes (2,4,5,17). Our previous work focused on CXC chemokines that contain a glutamic acid-leucinearginine (ELR) motif in their amino terminus, which confers binding specificity to the receptors CXCR1 and CXCR2 (2,17).…”
mentioning
confidence: 98%